1974
DOI: 10.1073/pnas.71.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Dependent Regulation of Insulin Receptor Concentrations: A Direct Demonstration in Cell Culture

Abstract: Using new methods (1-9), we and others have studied directly the binding of many polypeptide hormones to specific receptors on cells (10). The specificity of binding correlates well with the biological activity of the hormone. Typically, binding is rapid saturable, and reversible (e.g., Fig. 1) and represented as a simple biomolecular reaction, hormone + receptor T4 hormone-receptor complex. Recently, Archer, GoldfRne, Iahn, and others have found that the concentration of insulin receptors per cell fluctuates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
335
7
5

Year Published

1975
1975
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 945 publications
(383 citation statements)
references
References 33 publications
36
335
7
5
Order By: Relevance
“…Homologous insulin receptor up-regulation, as a result of decreased ambient insulin concentration, is the likely mechanism accounting for increased insulin receptor number in liver and kidney. This is confirmed by experiments performed in cultured cells [29,30]. With regard to the kidney, the present study demonstrates that insulin receptors are up-regulated in the renal cortex of insulin-deficient rats.…”
Section: Discussionsupporting
confidence: 76%
“…Homologous insulin receptor up-regulation, as a result of decreased ambient insulin concentration, is the likely mechanism accounting for increased insulin receptor number in liver and kidney. This is confirmed by experiments performed in cultured cells [29,30]. With regard to the kidney, the present study demonstrates that insulin receptors are up-regulated in the renal cortex of insulin-deficient rats.…”
Section: Discussionsupporting
confidence: 76%
“…In contrast, in vitro, the downregulation of IR has been demonstrated across several orders of magnitude of insulin concentration. 26 This observation therefore raises the possibility that the mechanisms of IR downregulation in vivo are more complex than those in tissue culture.…”
Section: Discussionmentioning
confidence: 95%
“…At least for the adipose tissue it may well be, as also suggested by Grey and Kipnis [40], that the diminished acute effect of insulin represents an adaptive phenomenon which is secondary to the hyperinsulinemia. It has indeed been shown that the presence of insulin during the culture of human lymphocytes leads to a diminished number of insulin receptors [41]. Whether a similar feedback mechanism exists for human fat cells is presently unknown but may well be the case.…”
Section: Discussionmentioning
confidence: 99%